2012
DOI: 10.3126/kumj.v9i1.6266
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Valve Repair: Devega’s Tricuspid Annuloplasty in Moderate Secondary Tricuspid Regurgitation

Abstract: Background Moderate secondary tricuspid incompetence has variable natural history if left unattended during mitral valve surgery. Recent data suggest progression of the secondary tricuspid incompetence over time. Secondary moderate tricuspid regurgitation in rheumatic mitral valve disease may regress after mitral valve surgery without direct intervention. Objectives: The present retrospective comparative hospital based tudy was done to assess early result of DeVega tricuspid valve annuloplasty amongst those wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
4
4
0
Order By: Relevance
“…Mechanical ventilation, ICU stay, and morbidity were not significant between both groups. Our results agreed with the study of Pradhan and coworkers [3]. Ro and colleagues reported that the operative mortality rate was 1.0%.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Mechanical ventilation, ICU stay, and morbidity were not significant between both groups. Our results agreed with the study of Pradhan and coworkers [3]. Ro and colleagues reported that the operative mortality rate was 1.0%.…”
Section: Discussionsupporting
confidence: 93%
“…We have found a significant difference in the functional class with better improvement in the repair group. Our results were supported by the study of Pradhan and colleagues who found that at three month's review after surgery, four patients were in NYHA II amongst those without tricuspid repair, whilst the rest were in NYHA I [3]. Additionally, DeMeester and coworkers reported that NYHA functional class was significantly better compared with preoperatively in all patients, at 6 months follow-up [11].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations